2015
DOI: 10.1053/j.gastro.2015.08.048
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Esophageal Adenocarcinoma and Causes of Mortality After Radiofrequency Ablation of Barrett’s Esophagus

Abstract: Background & Aims Radiofrequency ablation (RFA) is commonly used to treat Barrett's esophagus (BE). We assessed the incidence of esophageal adenocarcinoma (EAC) after RFA, predictors of EAC, and EAC-specific and all-cause mortality rates. Methods We assessed outcomes in a multicenter study of RFA for BE. Kaplan-Meier curves of EAC incidence were stratified by baseline histology. Crude EAC incidence and mortality (both all-cause and EAC-specific) rates were calculated, and adjusted all-cause mortality rates w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(48 citation statements)
references
References 34 publications
5
42
0
1
Order By: Relevance
“…Early detection and treatment of preneoplastic lesions also led to a reduction in the incidence of ESCC [89]. Similar to this, multiple studies have shown that treatment of dysplasia in BE patients - for example, with radiofrequency ablation (RFA) - reduces the risk of EAC [90,91,92]. RFA is an FDA-approved endoscopic technique in which diseased tissue is exposed to heat energy and destroyed.…”
Section: Prevention Of Esophageal and Gastric Cardia Cancersmentioning
confidence: 97%
See 1 more Smart Citation
“…Early detection and treatment of preneoplastic lesions also led to a reduction in the incidence of ESCC [89]. Similar to this, multiple studies have shown that treatment of dysplasia in BE patients - for example, with radiofrequency ablation (RFA) - reduces the risk of EAC [90,91,92]. RFA is an FDA-approved endoscopic technique in which diseased tissue is exposed to heat energy and destroyed.…”
Section: Prevention Of Esophageal and Gastric Cardia Cancersmentioning
confidence: 97%
“…This technique has been proven to be safe and durable at least through medium-term follow-up [93,94]. In a multicenter RFA study in the USA, among 4,982 patients with RFA treatment, the incidence of EAC was markedly lower than in other studies of disease progression [91]. A general consensus has been reached among gastroenterologists in Europe and the USA that endoscopic resection and ablation is the most effective therapy for high-risk BE [95].…”
Section: Prevention Of Esophageal and Gastric Cardia Cancersmentioning
confidence: 99%
“…As recommended by national and European guidelines, the current gold standard for mucosal ablation is radiofrequency ablation, but for small segments argon plasma coagulation can be used [41,42]. This strategy is both safe and effective resulting in minimally invasive treatment at early stage and thus fewer patients dying from OAC [43][44][45][46]. Treatment of LGD can be recommended under certain conditions, since it can be associated with significant progression rates.…”
Section: Endoscopic Treatment Of Precancerous and Earlymentioning
confidence: 99%
“…A study with data from the U.S. national RFA registry published in 2015 showed that after initiating treatment with RFA in patients with BE, the risk of incident EAC or death from EAC is small (7.8/1,000 person-years and 0.7/1,000 person-years, respectively), with lower EAC incidence rates compared to estimates derived from natural history studies when stratified by baseline histology and degree of dysplasia (54).…”
Section: Radiofrequency Ablation (Rfa)mentioning
confidence: 99%
“…A randomized, sham-controlled trial of RFA in BE noted presence of SSIM in 25% of cases prior to ablation, which decreased to 5% 12 months after ablation (10). A study published in 2015 from the U.S. RFA registry (54) demonstrated that SSIM was associated with an increased risk of EAC, but all subsquamous cancers occurred prior to CE-IM. After CE-IM, SSIM was much less common, suggesting that RFA may eradicate SSIM and prevent subsquamous cancers.…”
Section: Post-treatment Surveillancementioning
confidence: 99%